The History and Present State of Virginia : A New Edition with an Introduction by Susan Scott Parrish - Beverley, Robert, approximately 1673-1722 (Book collections on Project MUSE., 2013)
Written and published in London in 1705, this was one of the earliest printed English-language histories about North America by an author born there. Robert Beverley was a scion of Virginia's planter elite, ambitious and at odds with royal governors in the colony. As a native-born American he provided English readers with the first full account of the province's past, natural history, Indians, and current politics and society. This new edition places the author and his book in the context of the political and cultural issues of his day and explores the many contradictions embedded in his narrative.